'Clemency on the way to the gallows': death, dreams and dissociation†. Issue 5 (10th October 2017) - Kimmel, Kenneth
Abstract: The survivor of a decade of childhood sexual trauma and violence, perpetrated by a monstrous father, produced a series of dreams in the final year of a ten‐year analysis. They illuminated the 'death drive' beneath a lifelong preoccupation with dying and fantasies of submission to death, perpetuated by the promise of hoped‐for freedom from pain and release from a life of suffering. The initial dream involved the collapse of a team of white horses drawing him in a pillory cart to his own hanging for a crime he did not commit. It signified the collapse of a fragile psychological system based on his role as the 'sacrificial lamb, ' protecting a (not so) innocent mother. The raw truth was now unconcealed: primal, violent, and terrifying dreams and affects emerged where he was now the murderous aggressor. His dreams would become primary agents for an instinctive, life‐giving authenticity to emerge, offering him clemency from the shattering repetitions of persecution and dissociation.